2010
DOI: 10.1172/jci41129
|View full text |Cite
|
Sign up to set email alerts
|

Bestrophin-2 mediates bicarbonate transport by goblet cells in mouse colon

Abstract: Anion transport by the colonic mucosa maintains the hydration and pH of the colonic lumen, and its disruption causes a variety of diarrheal diseases. Cholinergic agonists raise cytosolic Ca 2+ levels and stimulate anion secretion, but the mechanisms underlying this effect remain unclear. Cholinergic stimulation of anion secretion may occur via activation of Ca 2+ -activated Cl -channels (CaCCs) or an increase in the Cl -driving force through CFTR after activation of Ca 2+ -dependent K + channels. Here we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
105
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 61 publications
6
105
0
Order By: Relevance
“…Recent studies have shown that a newly identified Clchannel, bestrophin2 (BEST2), is expressed specifically by colonic goblet cells [46,47]. Mice lacking BEST2 develops spontaneous colitis, and are more susceptible to DSS challenge, suggesting that this channel may play a distinct role to maintain goblet cell-dependent barrier functions [46]. We have further identified that BEST2 expression is down-regulated in the inflamed colonic mucosa of UC patients [47].…”
Section: Role Of Iecs In the Pathogenesis Of Ibdmentioning
confidence: 79%
See 1 more Smart Citation
“…Recent studies have shown that a newly identified Clchannel, bestrophin2 (BEST2), is expressed specifically by colonic goblet cells [46,47]. Mice lacking BEST2 develops spontaneous colitis, and are more susceptible to DSS challenge, suggesting that this channel may play a distinct role to maintain goblet cell-dependent barrier functions [46]. We have further identified that BEST2 expression is down-regulated in the inflamed colonic mucosa of UC patients [47].…”
Section: Role Of Iecs In the Pathogenesis Of Ibdmentioning
confidence: 79%
“…Besides mucin production, goblet cells secretes cytokines such as IL-7 [44] and thus may exert immunoregulatory functions, and can also deliver luminal antigens to the underlying DCs [45]. Recent studies have shown that a newly identified Clchannel, bestrophin2 (BEST2), is expressed specifically by colonic goblet cells [46,47]. Mice lacking BEST2 develops spontaneous colitis, and are more susceptible to DSS challenge, suggesting that this channel may play a distinct role to maintain goblet cell-dependent barrier functions [46].…”
Section: Role Of Iecs In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…Topical application of brinzolamide led to a greater decrease in IOP than was observed in Best2 ϩ/ϩ mice, suggesting a role for bicarbonate in these effects. Indeed, we have since shown that Best2 functions as a critical bicarbonate channel in colon goblet cells (10), and it is likely that it functions similarly in NPE cells. This led us to examine the role of sAC in regulation of IOP.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we demonstrated that bestrophin 2 (Best2) functions as a HCO 3 Ϫ channel in colon goblet cells (10). In the eye, Best2 is uniquely localized to the basal membrane of NPE cells (11,12).…”
mentioning
confidence: 99%
“…Also, the possibility of bestrophins forming heteromeric complexes in native tissues is limited due to their restricted distribution. The hBest1 mainly expresses in retina and RPE cells (1,11,44), whereas hBest2 and hBest4 express mostly in different cell types in colon (goblet cells and small intestine, respectively) (45,46).…”
Section: Discussionmentioning
confidence: 99%